Effects of on- and off-year management practices on the soil organic C fractions and microbial community in a Moso bamboo (Phyllostachys edulis) forest in subtropical China - Huang, Zhiyuan; Li, Qiaoling; Gai, Xu; Zhang, Xiaoping; Zhong, Zheke; Bian, Fangyuan; Yang, Chuanbao (Frontiers in Plant Science, 2022)
On- and off-year management practices are usually adopted in Moso bamboo (Phyllostachys edulis) forests to achieve higher productivity. However, little is known about the effects of these management practices on soil C sequestration and microbial community structure. In the present study, soil nutrient content, organic C fractions, and bacterial and fungal communities were comparatively investigated in on- and off-year bamboo stands. The results showed that soil organic C (SOC), alkali-hydrolyzable N (AN), and available P (AP) in the on-year were significantly lower (p ≤ 0.05) than those in the off-year. Among the different soil organic C fractions, easily oxidizable organic C (EOC), microbial biomass C (MBC), Ca-bound SOC (Ca-SOC), and Fe/Al-bound SOC (Fe/Al-SOC) also had significantly higher contents in the off-year than in the on-year, with MBC and EOC decreasing by 56.3% and 24.5%, respectively, indicating that both active and passive soil organic C pools increased in the off-year. However, the alpha diversities of both soil bacteria and fungi were significantly lower in the off-year soils than in the on-year soils. The bacterial taxa Actinobacteria, Planctomycetes, WPS-2, Acidothermus, Candidatus_Solibacter, Burkholderia-Caballeronia-Paraburkholderia, and Candidatus_Xiphinematobacter were increased in off-year soils relative to on-year soils. Meanwhile, fungal taxa Ascomycota, Mortierella, Hypocrea, Cryptococcus, Clitopilus, and Ceratocystis were significantly increased in on-year soils. Soil pH, SOC, AP, MBC, EOC, and Ca-SOC were significantly correlated with bacterial and fungal communities, with soil pH being the most important driving factor for the shift in bacterial and fungal communities. Our findings showed that the studied bamboo forest possessed an inherent restorative ability in the off-year, which can reverse the soil nutrient and C depletion in the on-years and ensure soil fertility in the long term.